Optimizing the stabilization techniques and enhancing the oil yield of Foxtail Millet Bran (FMB) - Preeti, Kittur; Meenakshi, V; Vijayalakshmi, R; Mini, M L; Kalaiselvan, A; Sakthi, S T (Plant Science Today, 2025)
Millet bran, a by-product of preliminary processes is often discarded or utilised as animal feed. Despite of the nutritional advantage, the main challenge in using bran as food is due to its shortened shelf life. Stabilization of bran is essential to prevent hydrolytic rancidity and free fatty acid (FFA) formation by inactivating lipase enzymes. FMB was stabilized by three methods viz., microwave (900 W, 2450 MHz), ultrasonication (500 W, 40 KHz) and blanching. Lipase activity and oil yield were studied. FMB was stabilized by microwave technique, maintaining an initial moisture to 21 % for 1 min (MT1), 2 min (MT2), 3 min (MT3) and ultrasonication for 20 min (UT1), 40 min (UT2), 60 min (UT3) and blanching for 20 min (BT1), 40 min (BT2), 60 min (BT3) followed by cabinet drying. Lipase activity was measured in control and stabilized millet bran. Lipase activity of control (untreated bran) was 0.01 and it was reduced to 0.0005, 0.001, 0.0003, 0.00042 and 0.0001 in UT1, MT1, MT2, BT1 and BT2 respectively. Lipase activity was found to be nil in UT2, UT3, MT3 and BT3. Oil yield was found to be increased in stabilized bran from 10.13 % (MT2) to 10.95 % (MT3) compared to control (10.01 %). Changes in nutritional characteristics of stabilised FMB were studied. In stabilised FMB increase in protein content a decrease in moisture, ash and fiber was observed in MT3. In conclusion, microwave (MW) treatment for stabilization of FMB significantly improved the stability and oil yield. The emerging debranning and stabilizing technologies may accelerate the utilization of millet bran for industrial application.